Carbon Footprint Management with Industry 4.0 Technologies and Erp Systems in Sustainable Manufacturing - Yüksel Yurtay (Applied Sciences)
The urgency of addressing climate change has amplified the need for sustainable manufacturing practices. This review explores the integration of carbon footprint management and energy efficiency strategies within Industry 4.0 technologies and ERP systems, emphasizing their role in achieving environmental sustainability. Despite the increasing interest in these domains, the literature reveals critical gaps, particularly in the application of Industry 4.0 technologies—such as IoT, big data analytics, and AI—for effective carbon management and sustainable manufacturing. Furthermore, the limited exploration of ERP systems in tracking, analyzing, and optimizing carbon emissions across supply chains highlights another under-researched area. This paper systematically reviews recent advancements, methodologies, and implementation challenges, categorizing findings under energy efficiency strategies, green supply chain management, and digital transformation for carbon reduction. The study identifies opportunities for real-time monitoring, predictive analytics, and cross-sector collaborations while addressing obstacles such as high initial costs, data integration complexities, and the lack of regulatory frameworks. By bridging these research gaps, this paper contributes a comprehensive understanding of how Industry 4.0 technologies and ERP systems can transform carbon footprint management, providing actionable insights for academia, policymakers, and industry practitioners aiming to align with global sustainability goals.